Peran Guru Bimbingan Konseling dalam Mengatasi Kesulitan Belajar Siswa pada Mata Pelajaran Fisika di SMA Negeri 7 Maluku Tengah - Augia Tuapetel; Friska Siwabessy; Heince Uktolseja; Damasena Lerebulan; Cindya Margaret Mirpey; Florentina Selvia Renwarin (Journal on Education, 2025)
This study aims to identify and analyze the role of guidance and counseling teachers in overcoming students' learning difficulties in physics at SMA Negeri 7 Maluku Tengah. The background of this research is the fact that physics is often perceived as a difficult subject by most students, which negatively affects their academic achievement. This study employs a descriptive qualitative approach, using data collection techniques such as observation, in-depth interviews, and documentation. The informants in this study include the guidance and counseling teacher (BK), the physics teacher, and students from class XI IPA 2. The findings reveal that the BK teacher plays a central role as a facilitator, motivator, and mediator in addressing students' learning barriers. These learning difficulties are caused by internal factors (lack of motivation, inability to understand formulas) and external factors (teaching methods, unsupportive learning environment). The BK teacher helps students identify the problems they face, build self-confidence, and encourages them to engage actively in the learning process. This study emphasizes the importance of collaboration between the BK teacher, subject teachers, and students in creating a conducive learning environment